Optimizing Phaeodactylum tricornutum cultivation: integrated strategies for enhancing biomass, lipid, and fucoxanthin production - Mostafa E. Elshobary; Walaa A. Abo-Shanab; Stephan S. W. Ende; Mohammed Alquraishi; Rania A. El-Shenody (Biotechnology for Biofuels and Bioproducts)
Abstract Background Phaeodactylum tricornutum is a versatile marine microalga renowned for its high-value metabolite production, including omega-3 fatty acids and fucoxanthin, with emerging potential for integrated biorefinery approaches that encompass biofuel and bioproduct generation. Therefore, in this study we aimed to optimize the cultivation conditions for boosting biomass, lipid, and fucoxanthin production in P. tricornutum, focusing on the impacts of different nutrient ratios (nitrogen, phosphorus, silicate), glycerol supplementation, and light regimes. Results Optimized medium (− 50%N%, + 50% P, Zero-Si, 2 g glycerol) under low-intensity blue light (100 μmol m⁻2 s⁻1) improved biomass to 1.6 g L⁻1, with lipid productivity reaching 539.25 mg g⁻1, while fucoxanthin increased to 20.44 mg g−1. Total saturated fatty acid (ΣSFA) content in the optimized culture increased approximately 2.4-fold compared to the control F/2 medium. This change in fatty acid composition led to improved biodiesel properties, including a higher cetane number (59.18 vs. 56.04) and lower iodine value (53.96 vs 88.99 g I2/100 g oil). The optimized conditions also altered the biodiesel characteristics, such as kinematic viscosity, cloud point, and higher heating value. Conclusion Our optimization approach reveals the significant potential of P. tricornutum as a versatile microbial platform for biomass, lipid, and fucoxanthin production. The tailored cultivation strategy successfully enhanced biomass and lipid accumulation, with notable improvements in biodiesel properties through strategic nutrient and light regime manipulation. These findings demonstrate the critical role of precise cultivation conditions in optimizing microalgal metabolic performance for biotechnological applications.